Intertrochanteric curved varus osteotomy for subchondral fracture of the femoral head: a case series - Keiji Otaka; Yusuke Osawa; Yasuhiko Takegami; Taisuke Seki; Shiro Imagama (Arthroplasty, 2023)
Abstract Although favorable results have been reported with total hip arthroplasty, joint-preserving treatment should be the first choice for subchondral fracture of the femoral head (SFF) in young patients. This study reviewed four young male patients with SFF who underwent intertrochanteric curved varus osteotomy (CVO). The patients had a mean age of 32.3 years (range: 18–49 years). Conservative treatment was initially attempted in all cases, but failed to alleviate the pain, leading to surgical intervention at an average time of 6 months (range: 4–10 months) after symptom onset. As the fracture sites were located medial to the lateral edge of the acetabulum in all cases, CVO was performed to achieve a postoperative intact ratio of ≥ 34% in the weight-bearing region of the femoral head. The average follow-up period after surgery lasted 4.3 years (range: 2–7 years). Clinical and radiographic assessments were performed pre- and postoperatively. At the latest follow-up, the mean Harris hip score improved from 67.3 preoperatively to 99.5 postoperatively. The average preoperative intact ratio of the weight-bearing region of the femoral head was 12.3%, which increased to 44.3% postoperatively. No progression to femoral head collapse or joint space narrowing was observed on the plain radiographs. CVO is a simple, less-invasive, and beneficial approach for treating SFF in young patients whose fractures occur medial to the lateral edge of the acetabulum.